Atypical Endoleak Associated With Inadvertent Cannulation of the Ipsilateral Gate in an Ovation Trimodular Stent-Graft. (February 2018) - Maleux, Geert; Houthoofd, Sabrina; Poorteman, Lien; Fourneau, Inge
We report on a 54-year-old man who presented with an atypical, proximal, intraoperative endoleak after endovascular aortic repair with an Ovation endograft for a 65-mm-diameter abdominal aortic aneurysm. The endografting was complicated by inadvertent bilateral iliac limb insertion into the right gate without cannulation of the left gate. The endoleak was treated by brachial approach: Through the open left gate, the outflow inferior mesenteric artery was coil embolized and the inflow left gate was closed with an Amplatzer plug. Follow-up computed tomography over 3 years showed absence of any endoleak and a stable diameter of the excluded abdominal aortic aneurysm.